PEMBELAJARAN ERA DIGITAL 5.0: PEMBENTUKAN KARAKTER POLA PIKIR CERDAS DI KALANGAN MAHASISWA PENDIDIKAN BAHASA dan SASTRA INDONESIA - Dewi Sartika; Hasnah Fauziah; Lisda Togatorop; Farel Olva Zuve (UNIVERSITAS PGRI YOGYAKARTA, 2026)
This study aims to examine the influence of the Digital Era 5.0 on the formation of character and intelligent mindset among students of the Indonesian Language and Literature Education Study Program. The background of this research is rooted in the increasing intensity of students’ interaction with digital media and advanced technologies, which potentially shape their ways of thinking, attitudes, values, and academic as well as social behavior. This study employs a descriptive qualitative approach. Data were collected through questionnaires, in-depth interviews, and documentation involving students who actively use digital media in their academic and daily lives. The data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that digital media in the Digital Era 5.0 has a significant influence on students’ character formation and intellectual mindset. This influence is largely determined by students’ levels of digital media literacy and reflective ability. Students with high digital media literacy tend to demonstrate critical thinking skills, selective information processing, and ethical awareness, enabling them to utilize digital media for academic development and character building. Conversely, students with low digital media literacy are more susceptible to negative influences, such as misinformation, superficial thinking patterns, and the decline of academic ethics. Therefore, the Digital Era 5.0 holds considerable potential in shaping an intelligent, critical, and character-driven generation, provided that it is supported by the integration of digital media literacy and character education within higher education learning processes.